The Flying Carpet Supplementary Reading Material - Roderick Hunt (Oxford Reading Tree, 1990)
The Flying Carpet Teaching Notes Author: Thelma Page ... Group or guided reading Introducing the book and talk about the picture on the cover. Look briefly